Influência de medicamentos antialérgicos usados sistemicamente no processo de reabsorção radicular em dentes reimplantados tardiamente: estudo em ratos - MACHADO, Nathália Evelyn da Silva (2019)
Backgroud/Aim: One of the undesirable consequences of tooth replantation is root resorption, and the search for therapeutic alternatives for the prevention or treatment of tooth reimplantation is essential to increase the survival rates of reimplanted teeth. It is known that the use of glucocorticosteroids or leukotriene inhibitors, known antiallergic agents, can contribute to the control of bone resorption and, due to the similarity between bone and root resorption processes, it was conceived to associate these systemic agents with the therapeutic protocol recommended for later reimplanted teeth. Thus, the objective of this work was to analyze the action of antiallergic agents systemically used on the root resorption process of late reimplanted teeth. Material and methods: Thirty-two upper right incisors of rats were used, which were extracted and reimplanted late, according to the protocol of the International Association of Dental Trauma (IADT); The animals were then divided into four groups: in group I (DEX), the animals were treated systemically with glucocorticosteroid; in groups II (Q) and III (OM), the animals were treated systemically with leukotriene inhibitors (Quercetin and Montelukast sodium respectively), and in group IV (C), the animals received no experimental systemic treatment. After 60 days of dental reimplantation, the animals were euthanized and the pieces obtained were processed in a histotechnic laboratory for microscopic, morphometric and immunohistochemical analysis. Results: Statistically significant difference between groups Q and MO for the presence of dental ankylosis and inflamed connective tissue (p <0.05) was observed statistically between the experimental groups and histological events. showed a statistically significant difference (p> 0.05). The immunohistochemical analysis revealed a difference for CD45 immunolabeling between the groups DEX and Q with group C. There was no interference in the root resorption process (p> 0.05). Conclusion: It can be concluded that the antiallergic agents used systemically do not present action on the root resorption process of late reimplanted teeth.